Experimental insight into the evolutionary mechanism of solid-to-hollow hydrogel. Issue 76 (6th September 2019) - Chen, Qing; Tan, Huiyan; Tu, Yaqing; Zhang, Lidong
Abstract : The evolutionary mechanism of solid-to-hollow sodium alginate hydrogel is reported, which provides a promising concept or method basis for the preparation of hollow hydrogels with sophisticated geometries. Abstract : We for the first time disclose the evolutionary mechanism of solid-to-hollow sodium alginate (SA) hydrogel in an aqueous solution of Cu 2+, H2 O2 and Tris–HCl elements, where the oxidative degradation and gas bubble assistance result in the hollow structures. This provides a promising concept or method basis for the preparation of hollow hydrogels with sophisticated geometries.